Influence of sampling location on physical and mechanical properties of full grain leather : Utjecaj mjesta uzorkovanja na fizikalna i mehanička svojstva koža punog prirodnog lica - Tomljenović, Antoneta (Array, 2021)
Full grain leather refers to the strongest and most durable part of the cattle hide, consisting of the grain layer and the part of the underlying corium, and has not been sanded or buffed to remove any imperfections, that means it displays the more natural characteristics of leather. Leather quality changes with sampling location, depending on variation present in the leather fibrous structure. Leather properties were also affected by tanning and finishing processes utilized during production. Full grain leather, instead finishing, sometimes go only through an ironing process for the desired sheen is obtained. Therefore, with the purpose of analysing the influence of the leather processing level, and sampling location on their quality, in this paper, the physical and mechanical properties of differently (synthetic and chromium) tanned finished and non-finished cattle full grain leathers, sampled from the bend, shoulder and belly of side leather cuts were evaluated. Their applicability for footwear uppers were assessed by measuring leather thickness, mass per unit area, apparent density, tensile strength and percentage elongation at break, all according to the standardised test methods.